2020
DOI: 10.3390/app10093266
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Magnetic Field in 400 kV Double-Circuit Transmission Lines

Abstract: A high-voltage AC double-circuit 400 kV overhead power transmission line runs from the city of Elk (Poland) to the city of Alytus (Lithuania). This international 400 kV power transmission line is potentially one of the strongest magnetic field-generating sources in the area. This 400 kV voltage double-circuit overhead transmission line and its surroundings were analyzed using the mathematical analytical methods of superposition and reflections. This research paper includes the calculation of the numerical valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…These limits are determined based on the physiological effects of these radiations and are detailed by the WHO (World Health Organization), ICNIRP (International Commission on Non-Ionizing Radiation Protection) and also at EU (European Union) level [12,13]. In the case of the electric field, its physiological effects are based on surface charge accumulation.…”
Section: Problem Identification-materials and Methodsmentioning
confidence: 99%
“…These limits are determined based on the physiological effects of these radiations and are detailed by the WHO (World Health Organization), ICNIRP (International Commission on Non-Ionizing Radiation Protection) and also at EU (European Union) level [12,13]. In the case of the electric field, its physiological effects are based on surface charge accumulation.…”
Section: Problem Identification-materials and Methodsmentioning
confidence: 99%
“…The frequency response of modal impedances of 440, 500, 765 and 1200 kV transmission lines with different tower configurations [19,20,[26][27][28][29] Figure 18. It can be observed that the frequency at which the slope changes occur is different for different lines but the number of positive and negative peaks are same for all the lines.…”
Section: Analysis Of Modal Impedancesmentioning
confidence: 99%
“…The proposed enhancements avoid the window approach and corresponding exhaustive search needed in [16]. The enhanced algorithm has been applied to single circuit 440 kV line with delta conductor configuration [19], single and double cirucit 765 kV line with delta and flat conductor configuration [20] and single circuit 1200 kV line with flat conductor configuration [20] transmission lines and the LPFD models are simulated in EMTP-RV. Switching transients in a 11-bus 4-generator 500 kV network are also simulated by replacing all the lines in the network by the proposed model [21].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these circuits will cause a magnetic field in its environment, and since these are small distances, the total field in the vicinity of such transmission line will be enlarged with their contributions [17], [18]. This means that fields of significantly higher intensity will appear compared to those that would be generated by all transmission lines individually.…”
Section: Introductionmentioning
confidence: 99%
“…This means that fields of significantly higher intensity will appear compared to those that would be generated by all transmission lines individually. Given the prescribed allowable field values, in the design stage and during the operation of power facilities, it is necessary to perform calculations, measurements or prediction of the generated field intensities [17], [19], [20]. The field intensity can be reduced by increasing the height of the towers.…”
Section: Introductionmentioning
confidence: 99%